(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
Trace element profiling analyzes the concentration and distribution of essential minerals and micronutrients within plant biomass. This study examined the inorganic constituents of Ficus exasperata by profiling its Milled-Wood Residue (MWR) and Extracted Lignin (EL). Three trees aged 18, 20, and 25 years were felled from the Arboretum of the Forestry Research Institute of Nigeria, Ibadan. Their merchantable lengths were 3.78 m, 3.50 m, and 3.60 m, with diameters at breast height of 15.8, 18.46, and 20.05 cm, respectively. Discs were collected at the base (10%), middle (50%), and top (90%) along the sampling height. Lignin extraction and silica (Si) content were determined using standard procedures. Atomic Absorption Spectrophotometry (AAS) was employed to quantify manganese (Mn), aluminum (Al), calcium (Ca), magnesium (Mg), zinc (Zn), lead (Pb), iron (Fe), and copper (Cu). Data were analyzed using Analysis of Variance. Results revealed that Si, Mn, and Pb were absent in EL but Si was 6.11% in MWR at the top wood. Calcium exhibited the highest concentration (68.89%) at the mid-wood in MWR, while EL recorded 10% at the top. Al, Mg, and Pb had the lowest contents, ranging from 0.01–0.05%. These findings establish a baseline elemental profile of Ficus exasperata MWR and EL, indicating its potential for applications in pulp production, bioenergy generation, and sustainable material technologies.